Out in the Cold: Identification of Genomic Regions Associated With Cold Tolerance in the Biocontrol Fungus Clonostachys rosea Through Genome-Wide Association Mapping - Broberg, Martin; Dubey, Mukesh; Sun, Man-Hong; Ihrmark, Katarina; Schroers, Hans-Josef; Li, Shi-Dong; Jensen, Dan Funck; Brandström Durling, Mikael; Karlsson, Magnus (Frontiers in Microbiology, 2018)
There is an increasing importance for using biocontrol agents in combating plant diseases sustainably and in the long term. As large scale genomic sequencing becomes economically viable, the impact of single nucleotide polymorphisms (SNPs) on biocontrol-associated phenotypes can be easily studied across entire genomes of fungal populations. Here, we improved a previously reported genome assembly of the biocontrol fungus Clonostachys rosea strain IK726 using the PacBio sequencing platform, which resulted in a total genome size of 70.7 Mbp and 21246 predicted genes. We further performed whole-genome re-sequencing of 52 additional C. rosea strains isolated globally using Illumina sequencing technology, in order to perform genome-wide association studies in conditions relevant for biocontrol activity. One such condition is the ability to grow at lower temperatures, as these will be prevalent for protecting growing crops in temperate climates. Growth rates at 10°C on potato dextrose agar of the 53 sequenced strains of C. rosea were measured and ranged between 0.066 and 0.413 mm/day. Performing a genome wide association study, a total of 1478 SNP markers were significantly associated with the trait and located in 227 scaffolds, within or close to (<1000 bp distance) 265 different genes. The predicted gene products included several chaperone proteins, membrane transporters, lipases and proteins involved in chitin metabolism with possible roles in cold tolerance. The data reported in this study provides a foundation for future investigations into the genetic basis for cold tolerance in fungi, with important implications for biocontrol.